Survey of Irish general practitioners' preferences for continuing professional development. Issue 1 (2nd January 2018) - Maher, B.; O'Neill, R.; Faruqui, A.; Bergin, C.; Horgan, M.; Bennett, D.; O'Tuathaigh, C. M. P.
Abstract: Background: Doctors' continuing professional development (CPD) training needs are known to be strongly influenced by national and local contextual characteristics. Given the changing national demographic profile and government-mandated changes to primary care health care provision, this study aimed to investigate Irish General Practitioners' (GPs) perceptions of, and preferences for, current and future CPD programmes. Methods: A cross-sectional questionnaire, using closed- and open-ended questions, was administered to Irish GPs, focusing on training needs analysis; CPD course content; preferred format and the learning environment. Results: The response rate was 719/1000 (71.9%). GPs identified doctor-patient communication as the most important and best-performed GP skill. Discrepancies between perceived importance (high) and current performance (low) emerged for time/workload management, practice finance and business skills. GPs identified clinically-relevant primary care topics and non-clinical topics (stress management, business skills, practice management) as preferences for future CPD. Flexible methods for CPD delivery were important. Gender and practice location (urban or rural) significantly influenced CPD participation and future course preference. Conclusion: The increasing diversity of services offered in the Irish primary care setting, in both clinical and non-clinical areas, should be tailored based to include GP practice location and structure.